Good Governance Practices by Local Organization in Forest Resource Management - Rosyadi, Slamet (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2013)
Centralized approach is no longer perceived as effective in managing natural resources such as the forest. In line with the good governance movement, practices of forest resource management have changed from one-bureaucratic show into partnership. Consequently, the concept of transparency, accountability, and broader public participations should be institutionalized to improve the sustainability of forest management. By using the experience of Banyumas’ forest communities as case studies, this research aims to examine the extent to which the practice of good governance in forest management develops and influences the sustainability of forest management. Since this study was been intended to reveal the process of governance practices at the level of community-based organization, it uses the descriptive-qualitative approach in its analysis. The result of this study shows that participatory forest monitoring, transparency and accountable asset utilization have been practiced by the local forestry organization in their forest management. The researcher also found that strong traditions and local leadership contributes positively to good governance practices by providing cultural dialogue forum, social control and a spirit of volunteering.